Why do molecules echo atomic periodicity?. Issue 17 (30th May 2013) - Hefferlin, Ray; Sackett, Jonathan; Tatum, Jeremy
<x xml:space="preserve">Abstract</x> Franck–Condon factors are investigated for sequences of free main‐group diatomic molecules. Theory‐based Condon loci (parabolas) and Morse‐potential loci are plotted on Deslandres tables to verify if they, indeed, follow the largest Franck–Condon factors. Then, the inclination angles of the Condon loci are determined. Thus, entire band systems are quantified by one variable, the angle. For all available isoelectronic sequences, this angle increases from a central minimum toward magic‐number molecular boundaries. The theory for the Condon locus gives the angle in terms of the ratio of the upper‐state to the lower‐state force constants. It is concluded that the periodicity is caused due to the fact that this ratio becomes larger as rare‐gas molecules are approached, a trend that probably points to the extreme cases of the rare‐gas molecules themselves. Thus, molecular periodicity echoes atomic periodicity in that data plots have extrema at molecules with magic‐number atoms, yet it does not echo the details of atomic periodicity in series between those molecules. © 2013 Wiley Periodicals, Inc.